Students’ Response on Mini Lecture (Cermin) Program on the Learning Intensity in Islamic Education - Rahayu, Santi (International Journal Labs, 2021)
In the current era of globalization, education is very important. If the education of a society develops well, then it is undeniable that the community will be more